Optimizing the Capital Structure of Coal Companies in Indonesia Towards the Implementation of Government Regulation No. 36 of 2023 concerning Foreign Exchange Proceeds from Exports - Heny Istiqomah; I Ketut Gunarta (Journal Research of Social Science, Economics, and Management, 2025)
This study examines the impact of Government Regulation No. 36 of 2023 on the financial structure of PT X, a coal mining company in Indonesia, and explores how the company can optimize its capital structure to adapt to the new regulation requiring exporters to deposit 30% of their export proceeds into a special account for a minimum of three months. The research uses a quantitative approach with financial modeling, supported by qualitative interviews with PT X’s finance team and management. The study aims to analyze the company's financial condition before and after the implementation of the regulation, focusing on sales, costs, and liquidity. It also utilizes linear programming optimization with Microsoft Excel's Solver to minimize capital costs and maximize company value. The results indicate a significant shift in PT X's capital structure, with increased debt in 2023 due to the need for short-term financing to comply with the new regulation. The optimization model helps reduce the company’s reliance on debt and improves its financial ratios, such as current ratio and debt-to-equity ratio. This study provides practical insights for stakeholders in managing financial decisions under regulatory constraints and contributes to the broader understanding of capital structure optimization in the mining sector.